(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2025)
The research aims to investigate the impact of credit risks on the banking liquidity of commercial banks (research sample) for the period (2012_2021) by finding a solution to the basic problem that was formulated by the question (Does credit risk affect the liquidity of banks in terms of its indicators in commercial banks, the research sample?) As the research is important in knowing the extent of the impact of credit risks on banking liquidity in commercial banks (research sample) and highlighting the importance of financial instruments and measures used in credit risks through their impact on the banking liquidity of commercial banks (research sample), the community of the commercial banking sector listed on the Iraq Stock Exchange was chosen to be the research community with (19) commercial banks, while the research sample was represented by (10) commercial banks, which were chosen using the multi-criteria intentional sample method and were determined based on providing annual data in an integrated manner during the period 2012-2021, and the number of views reached (100) views, and the research relied on the analytical study method in addition to adopting the financial analysis of the banks’ financial statements Commercial (research sample), and statistical methods were used represented by the (EXCEL) program and the panel data method was relied upon in analyzing the relationship between variables, testing the study hypotheses using the (E-Views) program, extracting the arithmetic mean, median, standard deviation, upper and lower limits for all variables, testing the correlation coefficient, and testing the stability of the data (staticity). The study reached a set of theoretical and applied conclusions.